Considerações acerca do plano de intervenção pedagógica: uma experiência no programa residência pedagógica (PRP) - SANTOS, Leila Pimentel dos (2025)
Intervention practices to improve reading and writing are of great importance for the development of children in the literacy phase, as they act as a reinforcement of this learning. In this sense, the Pedagogical Residency Program (PRP), of the Federal University of Pará, through the Interdisciplinary Literacy and Literacy subproject, aimed, in the period between 2023 and 2024, to promote the insertion of pedagogy residents in the school space for the development of activities aimed at to reading and writing. Therefore, this work aimed to describe the experiences lived in the PRP that involved training, observation and practical intervention in reading and writing for students in the first year of elementary school. We propose the following questions for this study: What is the PRP about and what contributions has it provided to pedagogy graduates in their initial training? How was the training carried out during the execution of the Program? How did the practical reading and writing intervention practices occur? The research is anchored in studies by Fiorin (2003), Freire (1996), Soares (2020), Silva (2003), Silva (2021), among others. The method used for this research included a bibliographic stage with a qualitative and descriptive approach with observations and notes in a field diary. It was found that the residents' interventions, based on the guidance received during the training, contributed significantly to the progress in reading and writing of children in the first year of elementary school.